A group-forming course content-focused icebreaker for life science classrooms - Adam J. Kleinschmit; Rebecca L. Sparks-Thissen; Sumali Pandey (Journal of Microbiology & Biology Education)
ABSTRACT Collaboration and communication are important competencies for undergraduate life science education, as noted in the Vision and Change in Undergraduate Biology Education report. However, initiating collaboration and communication in the classroom can be an anxiety-inducing experience for many students. In contrast to traditional-style icebreakers, we introduce a course content-focused icebreaker activity that served as a group-forming undertaking on the first day of class. We developed four sets of handouts (icebreaker tickets), each having a common course theme (e.g., microbiology, cell biology, physiological system infections/disorders, virology). Students were randomly provided with a ticket at the beginning of the course, and they worked to establish groups with their peers, based on their own interpretation of the ticket’s content and rationalization of a grouping scheme. Student feedback and engagement data collected from implementation at three independent institutions were largely positive, where students reported the activity to be an effective tool for building a course content-focused community of learners. The icebreaker tickets and instructor’s notes disseminated in this manuscript can be adapted to fit educators’ course goals and help set the tone for the first day of the class and beyond that fosters communication and collaboration among students.